Process capability index for AC transformer under electrical harmonics - Méndez-González, Luis Carlos (2018)
Nowadays, the quality of electronic devices is subjected to many variables such as electrical, thermal, mechanical and environmental factors. Voltage variation induced by electrical harmonics presented in the power lines is one of the main causes for electronic products to reduce their quality and performance in an operational environment. In this study, more significant variables are addressed, and a comparative study between voltage variations with and without electrical harmonics is presented. The case study presented in this paper is based on a transformer under voltage scenarios proposed in this study. The corresponding Cpk index in the transformer was estimated using a non-normal tool. The results of the case study showed that laptop computer under electrical harmonics has a lower Cpk rank and that Cpk value impacts directly the lifetime and performance of the device.